2020
DOI: 10.7759/cureus.10699
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Posterior Tibial Slope in Saudis: A Radiographic Study

Abstract: Aim The present study aimed to establish the normal range of the posterior tibial slope (PTS) angle in the Saudi adult population and to identify whether there was an association between the angle and gender or age. Materials and methods A total of 524 normal knee radiographs of 410 patients aged 18-85 years were included in the study. The PTS was measured using the anterior tibial cortex method. Data were matched with gender and age for statistical analysis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The posterior slope value was set up to replicate the natural slope up to 9°. Though 9° is slightly higher than what has been recommended, as noted by de Boer et al [11], this is in line with the patient population of this study [11, 36, 51] and occurred in only 15 patients (37.5%) in the AFIP group with an extremely high preoperative posterior tibial slope of [68–80°]. After the final verification of the planning, the cuts were performed using the robotic arm to complete the distal femoral cut first, the anterior and posterior cuts, and then the tibial cut.…”
Section: Methodssupporting
confidence: 92%
“…The posterior slope value was set up to replicate the natural slope up to 9°. Though 9° is slightly higher than what has been recommended, as noted by de Boer et al [11], this is in line with the patient population of this study [11, 36, 51] and occurred in only 15 patients (37.5%) in the AFIP group with an extremely high preoperative posterior tibial slope of [68–80°]. After the final verification of the planning, the cuts were performed using the robotic arm to complete the distal femoral cut first, the anterior and posterior cuts, and then the tibial cut.…”
Section: Methodssupporting
confidence: 92%
“…There was no correlation between age, gender and PTS angles. 18 The values showed the difference of PTS in Saudi people comparing to deferent communities. Therefore, more comprehensive studies to search for the reported difference and calculation of actual PTS number of the Saudi community are needed.…”
Section: Discussionmentioning
confidence: 94%
“…This study can serve as a reference when performing measurements of knee-related radiographic parameters. PTS, which directly re ects the bony morphology of the tibia articular surface, is known to exhibit signi cant inter-individual variability [12][13][14][15][16][17]. This variability in PTS is reported to have a substantial impact on joint biomechanics [23,[25][26][27]; on the other hand, it may also in uence the measurement accuracy of related radiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these characteristics become more evident in the proximal tibial surface. The morphology of the proximal tibial surface differs between the medial and lateral compartments of the knee, with noteworthy inter-individual differences [12][13][14][15][16][17]. Furthermore, as it directly mirrors the articular surface, its variability potentially affects the measurement outcomes of radiographic variables that include the joint line.…”
mentioning
confidence: 99%